Global burden, trends, and inequalities of ischemic heart disease among young adults from 1990 to 2019: a population-based study - Wu, Peng; Yu, Shuixiu; Wang, Jun; Zou, Shenglan; Yao, De-Shan; Xiaochen, Yuan (Frontiers in Cardiovascular Medicine, 2023)
Background Ischemic heart disease (IHD) is a major global health concern, and its burden among young adults aged 25–49 years remains underexplored. This study aims to provide a comprehensive assessment of the global burden and trends of IHD over the past 30 years (1990–2019) among this age group, as well as to analyze the health inequalities related to socioeconomic development. Methods Data from Global Burden of Disease Study 2019 (GBD 2019) were utilized to analyze the prevalence, mortality, and disability-adjusted life years (DALYs) rate of IHD among young adults globally. Joinpoint regression analysis was applied to examine the trends over the study period. Health inequality analysis was performed to investigate the disparities in IHD burden related to the Socio-Demographic Index (SDI) of countries. Results According to GBD 2019 data, in 2019, the global numbers of young adults with IHD cases, deaths, and DALYs were 18,050,671 (95% UI, 15,551,940–21,254,746), 597,137 (548,250–647,778), and 28,692,968 (26,397,448–31,178,464), respectively, accounting for 9.15%, 6.53%, and 15.7% of the total global cases. Over the past 30 years, the mortality [AAPC = −0.4%, 95% CI (−0.7% to −0.1%)] and DALYs rate [AAPC = −0.3%, 95% CI (−0.6% to −0.1%)] of IHD among young adults decreased, while the prevalence rate [AAPC = 0.4%, 95% CI (0.4%–0.4%)] and YLDs rate [AAPC = 0.4%, 95% CI (0.3%–0.4%)] increased. Furthermore, countries with lower levels of socio-demographic index (SDI) disproportionately bore a higher burden of IHD among young adults. The inequality slope index for young adult IHD shifted from −56.6 [95% CI (−480.4–370.2)] in 1990 to −583.0 [95% CI (−996.8 to −169.2)] in 2019, and the concentration index moved from −8.2 [95% CI (−8.5 to −7.9)] in 1990 to −13.2 [95% CI (−13.9 to −12.4)] in 2019. Conclusions While the mortality and DALYs rate of IHD among global young adults have decreased over the past 30 years, the degree of inequality related to SDI among countries has continued to increase. Decision-makers in various countries should allocate resources wisely and implement effective strategies to improve the burden of young adults IHD globally and address the health inequalities associated with it.